2003
DOI: 10.1002/pmic.200300490
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric proteome analysis for profiling temperature‐dependent changes of protein expression in wild‐typeCaenorhabditis elegans

Abstract: We investigated the effect of cultivation temperatures on the protein expression levels in the fourth larval stage of the postembryonic development of wild-type Caenorhabditis elegans by mass spectrometric proteome analysis. From the 64 protein spots that were investigated, 5 spots were found reproducibly differently expressed when proteome maps derived from animals kept at 15 degrees C and at 25 degrees C, respectively, were compared. Spots of heat shock proteins HSP 70 (CE18679 or CE09682) and HSP 16 (CE1424… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…For example, proteomic changes similar to those described here were shown in a study on the response to cold stress of livers of warm-adapted gilthead sea bream (Ibarz et al, 2010); a study on cultivation temperatures of wild-type C. elegans larvae also showed increasing levels of chaperones and IDH in response to cold (Madi et al, 2003).…”
Section: Cold Acclimationmentioning
confidence: 79%
“…For example, proteomic changes similar to those described here were shown in a study on the response to cold stress of livers of warm-adapted gilthead sea bream (Ibarz et al, 2010); a study on cultivation temperatures of wild-type C. elegans larvae also showed increasing levels of chaperones and IDH in response to cold (Madi et al, 2003).…”
Section: Cold Acclimationmentioning
confidence: 79%
“…[68]). More recently temperature-dependent and stage-specific changes in the proteome [69] or germ-line developmentrelated proteins [70] have been determined. Protein interaction maps for C. elegans, derived from high-throughput yeast two-hybrid screens, are also being generated [71].…”
Section: Reviewmentioning
confidence: 99%
“…Zebrafish, in response to cold temperature, increase specific antioxidant enzymes such as superoxide dismutase (SOD)-1 and SOD-2 (Malek et al 2004), and carp also show a specific gene expression profile in response to cold temperature that is reminiscent of those changes seen in calorically restricted mice (Gracey et al 2004;Han and Hickey 2005;Lee et al 1999Lee et al , 2000. C. elegans also displays a specific physiological change in response to cold temperatures (Madi et al 2003;Paul et al 2000), and it has even been noted that cold temperature is a type of mild stress, which suggests a possible hormetic effect. Wong et al have shown that clk-1 mutants are insensitive to temperature changes during embryogenesis, which demonstrates that developmental adjustments to changing temperatures is an active process requiring genes such as clk-1 (Wong et al 1995).…”
Section: Introductionmentioning
confidence: 99%